Analisis Perubahan Luas Lahan dan Produksi Bawang Merah Menggunakan Sistem Informasi Geografis di Kabupaten Brebes Tahun 2023-2024 - Nida Hanifah; Bambang Agus Herlambang; Ahmad Khoirul Anam (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Brebes Regency is one of the main national centers of shallot production in Indonesia, where agricultural land dynamics play a crucial role in sustaining production performance. Rapid infrastructure development and land-use change have raised concerns regarding the sustainability of shallot cultivation areas. This study aims to analyze spatial–temporal changes in shallot cultivated area and production in Brebes Regency during 2023–2024 and to examine the relationship between land area changes and production levels at the sub-district scale. A descriptive quantitative approach based on spatial analysis was employed using Geographic Information Systems (GIS). Spatial data consisted of administrative boundary maps, while non-spatial data included shallot cultivated area and production data obtained from the Brebes Regency Office of Agriculture and Food Security. Data integration and analysis were conducted using QGIS through attribute joining and inter-annual comparison. The results indicate that total shallot cultivated area increased from 26,331 ha in 2023 to 28,628 ha in 2024, accompanied by a significant rise in production from 289,942.05 tons to 409,106.90 tons. Spatial analysis reveals that major production centers remain concentrated in the central and northern sub-districts, particularly Wanasari, Larangan, Bulakamba, and Tanjung. Although a positive relationship between land expansion and production increase is evident, variations among sub-districts suggest that productivity and local conditions also play important roles. The findings highlight the effectiveness of GIS-based analysis in supporting spatially informed agricultural land management and policy formulation.